Penguatan Tujuan Pendidikan Bahasa Arab melalui Perspektif Tarbiyah Islamiyah - Evi Riani, Ahmad Ali Muzakki; Alwi Rosyid; Albarra Sarbaini (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
Arabic holds an important position in Islamic education as the language of the Qur'an and Hadith. However, the teaching of Arabic in Islamic educational institutions often focuses only on linguistic aspects, thus not fully achieving the goals of comprehensive Islamic education. This study aims to analyze the strengthening of Arabic language education objectives from the perspective of Islamic Tarbiyah. The method used in this study is qualitative, with a literature study and descriptive analysis approach. The analysis was conducted on relevant sources. The findings indicate that Arabic education within the framework of Islamic Tarbiyah not only emphasizes mastery of language skills but also the importance of shaping students' faith, morals, and Islamic character. The integration of tarbawi values into the objectives, materials, methods, and evaluation of learning becomes a key element in creating Arabic language education that is valuable and aligned with the goals of Islamic education. Its implications are expected to serve as a reference for curriculum development, teacher competence improvement, as well as the formulation of contextual, integrative, and sustainable Arabic language learning policies in national Islamic educational institutions.